2015
DOI: 10.1111/1346-8138.13030
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of botulinum toxin A on Raynaud's phenomenon in Japanese patients with systemic sclerosis: A prospective, case series study

Abstract: Currently, there is no satisfactory treatment for Raynaud's phenomenon (RP) in systemic sclerosis (SSc). Recently, it has been reported that botulinum toxin A (BTX-A) injection was effective for the treatment of RP in SSc patients. The objective was to assess the efficacy and safety of BTX-A on RP in Japanese SSc patients. In the prospective, case series study, 10 Japanese SSc patients with RP received 10 U of BTX-A injections into the hand. The change in severity of RP, including the frequency of attacks/pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(118 citation statements)
references
References 44 publications
2
108
1
7
Order By: Relevance
“…O protocolo utilizado neste estudo aplicou informações descritas na literatura que utilizam estresse ao frio para demonstrar o comportamento do FR [10], [16]- [20].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…O protocolo utilizado neste estudo aplicou informações descritas na literatura que utilizam estresse ao frio para demonstrar o comportamento do FR [10], [16]- [20].…”
Section: Discussionunclassified
“…A Na amostra geral a temperatura do dedo mínimo foi a mais baixa logo após o estresse em água fria (15,6 o C) e após dez minutos de recuperação (20,5 o C). A palma da mão obteve as temperaturas mais altas em ambos os momentos (20,3 o C e 25,9 o C respectivamente), conforme apresentado tabela 1.…”
Section: B Método De Aplicaçãounclassified
See 1 more Smart Citation
“…Therefore, in some studies the patients enrolled are not well identified as a primary or secondary RP. The prospective case series study by Motegi et al [97] is unique in that it enrolled 10 patients affected by RP concomitant to SSc and treated all of them with BoNT-A. All studies, summarized in Table 6 , enrolled only a few patients and are totally lacking a standardization injection protocol and outcomes.…”
Section: Raynaud Phenomenonmentioning
confidence: 99%
“…Systemic sclerosis (SSc) is a connective tissue disease characterized by the fibrosis of the skin and internal organs, microangiopathy and autoimmunity . SSc patients develop various microangiopathies, such as Raynaud's phenomenon (RP), nail fold capillary abnormality, persistent digital ischemia, acro‐osteolysis (AO) and digital ulcers (DU) . RP and nail fold capillary abnormality generally precede the onset of fibrosis by several months or years, suggesting that vascular disorder may be a primary event in the pathogenesis of SSc .…”
Section: Introductionmentioning
confidence: 99%